2006
DOI: 10.1044/1092-4388(2006/012)
|View full text |Cite
|
Sign up to set email alerts
|

Tinnitus and Its Effect on Working Memory and Attention

Abstract: Tinnitus and Its Effect on Working Memory and AttentionPurpose: In 2 experiments, the assumption that continual orienting to tinnitus uses cognitive resources was investigated. It was hypothesized that differences in performance of tinnitus and control groups would manifest during demanding or unfamiliar tasks that required strategic, controlled processing and that reduced performance was not related solely to levels of anxiety. Method: Nineteen participants with chronic, moderate tinnitus-matched with a contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
151
2
11

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(175 citation statements)
references
References 46 publications
11
151
2
11
Order By: Relevance
“…They interpreted this result in such a way that the deviant stimulus to the contra lateral ear was less effective in distracting the attention from the task performed in tinnitus patients. The deficits shown in the study by Rossiter et al (2006), who observed differences between tinnitus and control groups with regard to tasks requiring strategic controlled processing, could also be explained by the amount of attention paid to the tinnitus. In the paper by Stevens et al (2007), tinnitus affected the performance in an attention demanding task as well.…”
Section: Discussionmentioning
confidence: 85%
“…They interpreted this result in such a way that the deviant stimulus to the contra lateral ear was less effective in distracting the attention from the task performed in tinnitus patients. The deficits shown in the study by Rossiter et al (2006), who observed differences between tinnitus and control groups with regard to tasks requiring strategic controlled processing, could also be explained by the amount of attention paid to the tinnitus. In the paper by Stevens et al (2007), tinnitus affected the performance in an attention demanding task as well.…”
Section: Discussionmentioning
confidence: 85%
“…The performance of the tinnitus patients on memory test (PGIMS) was affected on subtests: mental balance (72% patients), attention & concentration (52%), immediate recall (68%), remote memory (44%), retention of dissimilar pairs (44%) and visual recognition of pictures (40%). The performance might be altered due to deviated attention 43,44 for auditory 15,39 and nonauditory sensory processing 45 , poor working memory 46 , word recall, plan execution 47 , remote memory or/and autobiographical memory 48 . It can be hypothesized that in tinnitus patients due the reduction of gray matter in the ventromedial prefrontal cortex that participates in auditory gating 20 there is disruption in the processing of information and working memory system 46 , the attention is focused to tinnitus 43 leading to cognitive inefficiency 15 .…”
Section: Discussionmentioning
confidence: 99%
“…The severity of the distress experienced from the tinnitus is determined not by the acoustic characteristics, such as pitch and loudness of tinnitus (Andersson, 2003; Henry & Meikle, 2000; Hiller & Goebel, 2007), but by the cognitive, emotional and behavioural reactions to it (Andersson, 2002; Andersson & Westin, 2008; Cima, Crombez, & Vlaeyen, 2011; McKenna, Handscomb, Hoare, & Hall, 2014). Many tinnitus patients suffer from insomnia (Cronlein et al, 2016), concentration difficulties (Hallam, McKenna, & Shurlock, 2004; Rossiter, Stevens, & Walker, 2006) or headaches (Langguth et al, 2015). Comorbid mental symptoms of anxiety, depression and post-traumatic stress are common (Fagelson, 2007; Hinton, Chhean, Pich, Hofmann, & Barlow, 2006; McCormack et al, 2015; Pattyn et al, 2016; Zoger, Svedlund, & Holgers, 2006).…”
Section: Introductionmentioning
confidence: 99%